PENGARUH GAYA KEPEMIMPINAN, KULTUR ORGANISASI, DAN SRUKTUR AUDIT TERHADAP KOMUNIKASI DALAM TIM AUDIT - Noor, Siti; Sinung, Didik (Universitas Muhammadiyah Magelang, 2008)
This research purpose to analysis the influence among variable of leadership style, organizational culture, and structure make an audit of communications in audit team. This sample researchis all auditor at 5 Office of Public Accountanting in Yogyakarta and 5 Office of Public Accountanting in Semarang. Method of data collecting used by questionaires or primary data obtained from perception of all pesponder to questions of where questionnaires distributed directly. Intake sample used by convenience sampling. From 90 disseminated, questioonaires 63 questionnaires. Method analysis the data used by descriptive statistic. Result the examinaion of normality data indicate that the distribution data normally, is up to standard to so that test the doubled regression and satistical test of t and f. Result test the F indicate that the F count > F of is tables, that is 5,930 > 2,7608. Analysis result obtained with the test R-square of equal to 57,8%. Result from this research indicae that the leadership style, organizational culture, and structure make an audit of to have an effect on positive and significant to communications in team make an audit, either through partial and simultan. Research is here in after suggested to extend the area survey and extend the object research.